Mrs. Chester Root and Mrs. John Goldsborough - Unknown:::Creator::::::::::::
Photograph shows Mrs. Chester Root posing with a newspaper while Mrs. John Goldsborough looks on. The large print on the newspaper reads: "Rainier Brewing Company" while a smaller headline above it reads: "Brewing operations commmence today."